Effect of Vitamin D Supplementation on Recurrence Risk in Graves’ Disease Measured By The GREAT Score at Dr. Mohammad Hoesin General Hospital Palembang - Ali Rabbani, Muhammad Iqbal; Anggraini, Ratna Maila Dewi; Kusnadi, Yulianto; Maritska, Ziske (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Graves’ disease is the most common cause of primary hyperthyroidism with a prevalence of approximately 0.5%, predominantly affecting women (female-to- male ratio 6–7:1) aged 35–40 years. Predictors of treatment outcomes and recurrence risk have been studied, among them the GREAT Score, which combines age, goiter size, FT4, and TRAb levels. The aim of this study was to analyze changes in the GREAT Score after the addition of vitamin D supplementation in Graves' disease patients at Dr. Mohammad Hoesin General Hospital, Palembang, within 3 months. This was a double-blind randomized clinical trial involving 30 patients with Graves’ disease, both inpatients and outpatients, who met the inclusion criteria. Patients were randomly assigned into two groups: the intervention group received10,000 IU of vitamin D, while the control group received placebo. Recurrence risk was assessed using the GREAT Score at the first and third months, and data were analyzed with SPSS v.25. Analysis using the Wilcoxon test showed no significant change in the GREAT Score for the vitamin D group (p=0.102). At the first month, the distribution was 53.3% class I, 40.0% class II, and 5.7% class III, while at the third month it was 40.0% class I, 40.0% class II, and 20.0% class III. In the placebo group, results were also not significant (p=0.480), with the first-month distribution of 33.3% class I, 40.0% class II, and 26.7% class III, and the third month 40.0% class I, 33.3% class II, and 13.3% class III. In summary, Vitamin D supplementation has no significant effect in reducing the recurrence of Graves' disease compared to placebo.